1996
DOI: 10.1001/archpsyc.1996.01830030072011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity of Pituitary βEndorphin to Ethanol in Subjects at High Risk of Alcoholism

Abstract: This study indicates that the pituitary beta-endorphin system, but not the adrenal cortisol system, of the HR subjects shows an enhanced sensitivity to ethanol, which may be an important factor in controlling ethanol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
124
0
8

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(142 citation statements)
references
References 51 publications
10
124
0
8
Order By: Relevance
“…Indeed, it was this basic work that led to the hypothesis that naltrexone might be clinically useful in treating alcohol dependence, hence the development of naltrexone is a good example of translational neuroscience. Examining the effects of alcohol consumption and naltrexone in high-risk individuals has further supported the idea that there may be a relative lack of basal b-endorphin release and that the opioid system is more sensitive to alcohol among high-risk subjects (Gianoulakis, 1996;Gianoulakis et al, 1996). Subjectively, some fraction of the rewarding effects of alcohol ingestion in high-risk subjects can be blocked by naltrexone (King et al, 1997).…”
Section: Table 1 Baseline Demographics and Clinical Characteristics Omentioning
confidence: 90%
“…Indeed, it was this basic work that led to the hypothesis that naltrexone might be clinically useful in treating alcohol dependence, hence the development of naltrexone is a good example of translational neuroscience. Examining the effects of alcohol consumption and naltrexone in high-risk individuals has further supported the idea that there may be a relative lack of basal b-endorphin release and that the opioid system is more sensitive to alcohol among high-risk subjects (Gianoulakis, 1996;Gianoulakis et al, 1996). Subjectively, some fraction of the rewarding effects of alcohol ingestion in high-risk subjects can be blocked by naltrexone (King et al, 1997).…”
Section: Table 1 Baseline Demographics and Clinical Characteristics Omentioning
confidence: 90%
“…Concerning the activity of the hypothalamic-pituitary-adrenal (HPA) system, lower levels of adrenocorticotropin (ACTH; Schuckit et al, 1988) and cortisol (Schuckit et al, 1987) were found after ingestion of the rather high dosage of 0.88 g/kg ethanol in sons of alcoholics compared to control males, while this difference was not apparent after 0.6 g/kg in the same studies. Another study found no cortisol changes after ingestion of 0.25, 0.5, and 0.75 g/kg ethanol, while a rise in b-endorphin after the medium and high dose was observed in offspring of alcoholics but not in control subjects (Gianoulakis et al, 1996). Stimulation of the HPA system by i.v.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, unaffected adult children of alcoholics have basal levels of ␤ -endorphin comparable to those of abstinent alcoholics and significantly lower than those of unaffected adults without a parental history of alcoholism (Gianoulakis et al 1989(Gianoulakis et al , 1996. When given alcohol, adult children of alcoholics also showed a significantly greater increase (i.e., a "normalization") of ␤ -endorphin levels (Gianoulakis et al 1989(Gianoulakis et al , 1996.…”
mentioning
confidence: 98%